Key Characteristics for Thermal Runaway of Li-ion Batteries. (February 2019) - Feng, Xuning; Zheng, Siqi; Ren, Dongsheng; He, Xiangming; Wang, Li; Liu, Xiang; Li, Maogang; Ouyang, Minggao
Abstract: The lithium ion batteries are having increasing energy densities, meeting the requirement from industry, especially for the electric vehicles. However, a cell with a higher energy density is more prone to thermal runaway. We analyze the key characteristics during thermal runaway to help better define battery thermal runaway. Three characteristic temperatures are regarded as the common features of thermal runaway for all kinds of lithium ion batteries. The underlying mechanisms for the three characteristic temperatures have been investigated by thermal analysis. The conclusion of the analysis set benchmarks for evaluating the thermal runaway behaviors of commercial lithium-ion batteries, and the proposed methodologies benefits further research and development of battery safety design for electric vehicles.